Investigation of the complement receptor 3 (CD11b/CD18) in human rectal epithelium. - Hussain, L A (1995)
Rectal and cervicovaginal mucosa are common routes of transmission of HIV, although the mechanism of transmission is unknown. We have investigated human rectal and cervicovaginal epithelia for the expression of complement receptors (CR) and cell adhesion molecules which may be involved in HIV and other infections. In rectal mucosa, CR3 was detected in the surface and crypt epithelial cells by immunohistology, using MoAbs to CD18 and CD11b in 10 out of 15 specimens. RNA transcripts encoding both CD11b and CD18 were also demonstrated in surface and crypt epithelial cells by in situ hybridization. Although CD11b was detected in the epithelial cells in three out of the 14 cervicovaginal specimens, we were unable to detect CD18. We suggest that expression of the CD11b/CD18 heterodimer might facilitate transmission of HIV by enhancing binding of HIV-antibody complexes in seminal fluid to epithelial cells. Alternatively, since intercellular adhesion molecule-1 (ICAM-1) is a receptor for CD11b/CD18, this may promote adhesion between epithelial cells and HIV-infected mononuclear cells in seminal fluid.